Successful conservative treatment for posterior cruciate ligament ganglion cyst; a simple approach to a very rare case: a case series - Maulana, Yovi; Phatama, Krisna Yuarno (International Journal of Research in Medical Sciences, 2021)
Posterior cruciate ligament (PCL) ganglion cyst is relatively uncommon compared to anterior cruciate ligament (ACL) ganglion cyst. The combined prevalence of all cruciate ganglion cyst (anterior and posterior combined) is ranging from 0.2%-1.9%. It is usually found as an incidental finding during MRI examination. PCL ganglion cyst may be asymptomatic, or it may present as variety of knee symptoms. To the authors’ knowledge, there is no consensus regarding its treatment. Previous case series suggest treatment of PCL ganglion by arthroscopic resection. However, in this case series, we present 4 cases of young patients with PCL ganglion cyst treated successfully by rest and bracing. After our series of conservative treatment, the patients reported satisfactory pain relief. This result suggests that symptomatic PCL ganglion cyst could be treated conservatively.